2003
DOI: 10.1016/s0194-59980300176-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms in Detoxification Enzymes as Susceptibility Factor for Head and Neck Cancer?

Abstract: OBJECTIVE: Impaired detoxification of carcinogens found in tobacco smoke appears to increase the risk for tobacco associated cancer. The objective of this study was to investigate concomitant polymorphisms in genes encoding for various detoxification enzymes in patients with head and neck squamous cell carcinoma (HNSCC). METHODS: In 187 patients with HNSCC and in 139 healthy control subjects, the polymorphisms of cytochrome P450 1A1 ( CYP1A1), cytochrome P450 2D6 ( CYP2D6), and glutathione S-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…GST activities toward CDNB did not differ between the cisplatin‐treated Gstm1 / Gstt1 ‐DKO and WT mice, suggesting that other GST family members or other enzymes involved in cisplatin metabolism may have a compensating mechanism. This result is consistent with those of previous studies, which found that those with GSTM1 null mutation had equivalent GST enzyme activity to individuals who had a functional GSTM1 enzyme 67,68 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GST activities toward CDNB did not differ between the cisplatin‐treated Gstm1 / Gstt1 ‐DKO and WT mice, suggesting that other GST family members or other enzymes involved in cisplatin metabolism may have a compensating mechanism. This result is consistent with those of previous studies, which found that those with GSTM1 null mutation had equivalent GST enzyme activity to individuals who had a functional GSTM1 enzyme 67,68 …”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with those of previous studies, which found that those with GSTM1 null mutation had equivalent GST enzyme activity to individuals who a functional GSTM1 enzyme. 67,68 NRF2 regulates the expression of numerous antioxidant genes that are vital for the cellular defense system, particularly in the management of oxidative stress. 69 GSTM1 is a direct target of NRF2.…”
Section: Discussionmentioning
confidence: 99%